An international review of autism knowledge assessment measures. (April 2017) - Harrison, Ashley J; Slane, Mylissa M; Hoang, Linh; Campbell, Jonathan M
Autism spectrum disorder-specific knowledge deficits contribute to current disparities in the timing and quality of autism spectrum disorder services throughout the United States and globally. This study conducted a systematic review of Western and International literature to examine measures used to assess autism spectrum disorder knowledge. This review identified 44 unique autism spectrum disorder knowledge measures across 67 studies conducted in 21 countries. Measures used in each study were evaluated in terms of psychometric strength. Of the 67 studies reviewed, only 7% were rated as using a measure with strong psychometric support compared to 45% that were rated as using a measure with no reported psychometric support. Additionally, we examined content overlap and subdomains of autism spectrum disorder knowledge assessed (e.g. etiology, symptoms) and cross-cultural adaptation procedures utilized in the field. Based on these findings, the need for a cross-culturally valid and psychometrically sound measure of autism spectrum disorder knowledge is discussed and recommendations for improving current assessment methods are presented, including suggestions for measure subdomains.